Best Answer

x^2 + 3x + 2/(-3x) - x^2 - 2=3x-2+2/(-3x)=3x-2-2/(3x)

Q: Simplify x squared plus 3x plus 2 divided by -3x minus x squared minus 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

answer is p/5. problem: {[(p^2)-3p]/[(p^2)-6p+9]}/{20/(4p-12)}

x^2-4x/x^2-6x+8 = x(x-4)/(x-2)(x-4) = x/(x-2)

x - 3

x - 2

7(3y-2)-(-4y+9)

Related questions

No

Factorise it: (x + 5)(3x - 8)

#

It simplifies to 5a+4 !

answer is p/5. problem: {[(p^2)-3p]/[(p^2)-6p+9]}/{20/(4p-12)}

x^2-4x/x^2-6x+8 = x(x-4)/(x-2)(x-4) = x/(x-2)

x-8

x - 3

7x + 8

4x + 20

x - 5

There are no like terms here.